A Pentalogy of Cantrell with Absent Limb at Jimma University Medical Centre, Ethiopia: A Case Report.: Pentalogy of Cantrell with Absent Limb - Girma, Anberbir; Tilahun, Temesgen; Debela, Dejene Tolossa (Ethiopian Journal of Reproductive Health, 2026)
Background: A rare and serious condition known as pentalogy of Cantrell affects roughly 5.5 out of every 1,000,000 live newborns. It is associated with five abnormalities: omphalocele, cardiac ectopia, absence of the anterior diaphragm, absence of the distal part of the sternum, and absence of the parietal diaphragmatic pericardium. Case Description: Our case reported a severe form of pentalogy of Cantrell categorized as class 1, having all five of the diagnostic defects and associated with absent limb (amelia). A 21-year-old primigravida mother of 8 months amenorrhea presented at our hospital for a regular antenatal care visit. Then a thorough obstetric ultrasound scanning was done and successfully established the pentalogy of Cantrell despite the third trimester's delayed diagnosis. Finally, the multidisciplinary team discussed with the mother and family about the severity of the case as well as its poor prognosis, and the pregnancy was terminated medically. Conclusion: In the context of the complicated pentalogy of Cantrell, this case highlights the vital importance of prompt prenatal screening, thorough counselling, and individualized management planning by a multidisciplinary team.